Remediation Model Used in a Pharmacy Calculations Course - Dana Brown (University of Minnesota Libraries Publishing, 2019)
Remediation is a required component of pharmacy programs. In a pharmacy calculations course, two student-centered models of remediation have been utilized. These models were a shift from an intensive, hands-on infrastructure of faculty and student engagement to a more student self-directed process.  The models utilized development of an individualized plan for each student, clearly outlined expectations, faculty availability for consultation, as well as flexibility in remote completion of the assigned activities.  Both models resulted in student success.     Article Type: Note